CURRENT TRENDS IN HEALTHCARE MANAGEMENT AND WAYS TO IMPROVE IT - Popova Nigina Aleksandrovna; Rustamova Maxfuza Maxmudovna (European Science Publishing, 2024)
The healthcare system in modern conditions is an important object of public administration. At the same time, its sustainable and effective development is limited by an insufficient level of public administration and problems of economic and social orientation. Today, there is a need to develop and implement more effective and flexible mechanisms for the implementation of government programs aimed at the development of healthcare. There is also a need to increase the financing of the industry from the state budget, increase human resources, technology and knowledge intensity of this industry, and increase the level of control over the targeted expenditure of budget funds.
Keywords: public administration, healthcare, medical institutions, legal regulation, management efficiency.